Hydrogen production with ultrahigh efficiency under visible light by graphene well-wrapped UiO-66-NH2 octahedrons. Issue 38 (25th September 2017) - Wang, Yang; Yu, Yu; Li, Rui; Liu, Huijin; Zhang, Wei; Ling, Lianjie; Duan, Wubiao; Liu, Bo
Abstract : The proposed electrons transfer mechanism for graphene well-wrapped UiO-66-NH2 octahedrons. Abstract : An efficient catalytic system and surface modification are considered as two important routes for the enhancement of MOF-based photocatalytic properties. Herein, we report a significant improvement in hydrogen production efficiency with MOFs achieved through both the abovementioned routes. With the newly developed highly efficient TEOA–ErB system, H2 generation rate on UiO-66-NH2 octahedrons could amount to 21.2 mmol h −1 g −1 . Then, based on this system, the interaction of the UiO-66-NH2 surface with graphene was judiciously controlled. The prepared graphene well-wrapped UiO-66-NH2 octahedrons, in which every face was in contact with graphene, led to the highest H2 production efficiency of 41.4 mmol h −1 g −1 . These findings suggest that MOFs could potentially evolve into highly efficient photocatalysts when incorporated into a proper system and further revealed that modifications on the surface of MOFs might result in a better inhibition of electron–hole recombination in H2 generation.